The Correlation of Social Support with the Quality of Life of the Elderly - Susanti Susanti; Silvia Mona (Lembaga Pengembangan Kinerja Dosen, 2025)
The low quality of life of the elderly is often associated with the function of the family and the social support they receive, which can come from a partner, family, or community. As many as 70% of the elderly experience a decrease in quality of life, especially feelings of isolation and lack of attention from other family members. Objective: To determine the correlation between social support and the quality of life of the elderly. This study used a correlation methodology with a cross-sectional design. The population in this study was all respondents in RT 035 Batam city Sub-district, Batam City, with a total of 45 elderly in March-April 2025. The sampling technique used was total sampling. Instruments used: SSQ-6 and WHOQOL-BREF. The findings indicated that, according to the frequency distribution of social support, the majority of social support was moderate for as many as twenty people (44.4%). In contrast, the frequency of quality of life was moderate for as many as twenty-two people (48.9%). After completing the data analysis, the p-value was determined to be 0.004. The conclusion indicates a significant connection between the presence of social support and the quality of life experienced by elderly individuals.